GAS CHROMATOGRAPHY-MASS SPECTROMETRIC ANALYSIS AND IDENTIFICATION OF BIOACTIVE CONSTITUENTS OF CATHARANTHUS ROSEUS AND ITS ANTIOXIDANT ACTIVITY - RANI, JYOTI; KAPOOR, MANISH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objectives of this study were analysis of the phytochemicals produced by two different Catharanthus roseus morphotypes, i.e., pink and white flowered and evaluate it morphologically and phytochemically in terms of total phenolic content (TPC), total flavonoid content (TFC), antioxidant properties, and gas chromatography-mass spectrometry (GC-MS) analysis. Methods: Methanolic extracts of both morphotypes were prepared by Soxhlet apparatus. After extraction, the extracts were filtered and solvent removed by rotatory evaporator. TPC was determined by Folin–Ciocalteu reagent method and TFC was estimated by aluminum chloride colorimetric method. Antioxidant and free radical scavenging activities were estimated by superoxide dismutase and 1,1-diphenyl-2-picrylhydrazyl assay. GC-MS analysis was performed at Central Instrumentation Laboratory/ SAIF, Panjab University, Chandigarh. Results: Pink-flowered C. roseus showed highest activities in terms of TPC, TFC, and antioxidant activity as compared to white-flowered C. roseus. 42 different bioactive compounds were detected in the methanolic extract of pink, while only 7 compounds were identified in white-flowered C. roseus. The identification was performed by GS-MS analysis mainly based on retention time, peak area, molecular formula, and molecular weight. Conclusion: The finding indicated that the pink-flowered C. roseus was phytochemically superior then the white one.